2021
DOI: 10.1177/10600280211028882
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Tocilizumab With High-Dose Corticosteroids in Patients Hospitalized for COVID-19 Hypoxic Respiratory Failure Improves Mortality Without Increased Infection Risk

Abstract: Background Severe hypoxic respiratory failure from COVID-19 pneumonia carries a high mortality risk. There is uncertainty surrounding which patients benefit from corticosteroids in combination with tocilizumab and the dosage and timing of these agents. The balance of controlling inflammation without increasing the risk of secondary infection is difficult. At present, dexamethasone 6 mg is the standard of care in COVID-19 hypoxia; whether this is the ideal choice of steroid or dosage remains to be proven. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Following the elimination of duplicates and screening of titles and abstracts, we evaluated 244 articles in full text. Among these, we found 43 eligible articles (5 RCTs, 16 cohort studies, 2 case-control studies, and 20 case reports) (Figure 1) (Salvarani et al, 2021;REMAP-CAP Investigators et al, 2021;Canziani et al, 2020;Menzella et al, 2020;Fisher et al, 2021;Campochiaro et al, 2020;Vazquez Guillamet et al, 2021;Rajendram et al, 2021;Huang et al, 2021;Galván-Román et al, 2021;Saffo et al, 2021;Somers et al, 2021;Brosnahan et al, 2021;Corominas et al, 2021;Cavalli et al, 2021;Abe et al, 2021;Patel et al, 2020;Mady et al, 2020;Bernardo et al, 2020;Morillas et al, 2020;Cascella et al, 2020;Al-Kaf et al, 2021;Eroglu et al, 2021;Kataoka et al, 2021;Kishaba et al, 2021;Leelayuwatanakul et al, 2021;McKenzie et al, 2021;Nourié et al, 2021;Ladna et al, 2021;Senegaglia et al, 2021;Thammathiwat et al, 2021;Lescure et al, 2021;Della-Torre et al, 2020;Gremese et al, 2020;Kyriazopoulou et al, 2021a;Bozzi et al, 2021;Franzetti et al, 2021;…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the elimination of duplicates and screening of titles and abstracts, we evaluated 244 articles in full text. Among these, we found 43 eligible articles (5 RCTs, 16 cohort studies, 2 case-control studies, and 20 case reports) (Figure 1) (Salvarani et al, 2021;REMAP-CAP Investigators et al, 2021;Canziani et al, 2020;Menzella et al, 2020;Fisher et al, 2021;Campochiaro et al, 2020;Vazquez Guillamet et al, 2021;Rajendram et al, 2021;Huang et al, 2021;Galván-Román et al, 2021;Saffo et al, 2021;Somers et al, 2021;Brosnahan et al, 2021;Corominas et al, 2021;Cavalli et al, 2021;Abe et al, 2021;Patel et al, 2020;Mady et al, 2020;Bernardo et al, 2020;Morillas et al, 2020;Cascella et al, 2020;Al-Kaf et al, 2021;Eroglu et al, 2021;Kataoka et al, 2021;Kishaba et al, 2021;Leelayuwatanakul et al, 2021;McKenzie et al, 2021;Nourié et al, 2021;Ladna et al, 2021;Senegaglia et al, 2021;Thammathiwat et al, 2021;Lescure et al, 2021;Della-Torre et al, 2020;Gremese et al, 2020;Kyriazopoulou et al, 2021a;Bozzi et al, 2021;Franzetti et al, 2021;…”
Section: Search Resultsmentioning
confidence: 99%
“…The results are shown in Supplementary Figure S1 (Supplementary Material S2, Appendix p1). Some studies reported only one outcome, and we assessed the risk of bias for the results-for instance, bias in the measurement of outcomes was not available for safety for the study of Brosnahan et al (2021) because they did not report it. For mortality outcomes, the methodological quality of 16 cohorts was moderate to high, and those of 2 case-control studies were moderate.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Low dose methylprednisolone has been defined as 40 mg IV daily for 5 days [ 5 ] and 80 mg IV daily for 8 days [ 6 , 7 ]. High dose methylprednisolone has been defined as 120–180 mg IV daily for 10 days [ 8 ], 250 mg IV every day for 3 days [ 9 ], 250–500 mg IV daily for 3 days followed by prednisone 50 for 10 days [ 10 ], and 1 mg/kg IV for ≥ 3 days [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that LDMP (< 1.36 mg/kg of absolute body weight/day), administered > 7 days from onset of symptoms was associated with prolonged survival compared to no methylprednisolone and no additional benefit with HDMP (≥ 1.36 mg/kg of absolute body weight/day) [ 12 ]. Interestingly, the studies with varying definitions of high dose and showed mortality benefit fit our actual weight-based definition of low dose [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the recent publication by Brosnahan et al 1 regarding the impact of tocilizumab with high-dose corticosteroids in COVID-19 hypoxic respiratory failure.…”
mentioning
confidence: 99%